A Study on Image Processing and Techniques - Dukitha, M; Leka, M (International Journal of Computer Sciences and Engineering, 2025)
the objective of this project was to investigate methods to recover the maximum amount of available information from an image. Some radio frequency and optical sensors collect large-scale sets of spatial imagery data whose content is often obscured by fog, clouds, foliage and other intervening structures. Often, the obstruction is such as to render unreliable the definition of underlying images. Various mathematical operations used in image processing to remove obstructions from images and to recover reliable information were investigated, to include Spatial Domain Processing, Frequency Domain Processing, and non-Abelian group operations. These imaging techniques were researched and their effectiveness determined. Some of the most effective techniques were selected, refined, extended and customized for this project. Several examples are presented showing applications of such techniques with the MATLAB code included. A new advanced image processing technique was developed, tested, and is being proposed for the removal of clouds from an image. This technique has been applied to certain images to demonstrate its effectiveness. The MATLAB code has been developed, tested and appended to this report.